The Evolution of State Tort Law for Judicial Error in Chile - Larroucau Torres, Jorge (2025)
Compensation for damages due to erroneous administration of justice in Chile has two regimes available to the victim. The first is of a special and restricted nature, as it is only applicable in criminal proceedings for manifestly erroneous or arbitrary actions, and has a constitutional and legal basis. The other, created by case law, considering rules of civiland administrative law, constitutes the general regime. This article analyzes both avenues for obtaining compensation, with special emphasis on theinstitution involved in the origin of the damage. The main rulings of Chilean courts are used as guides, which reflect the shift from a personalist conception, based on the idea of “judicial error”, to a functionalist approach, based on the notion of error in the administration of justice.